Consumer Taxes on Alcohol: Is the Wine Sector a Niche Within the Alcoholic Beverages? - Paola Corsinovi (Italian Economic Journal, 2021)
As alcoholic beverages play a significant role in social and economic contexts, the taxation of alcohol and its policy regulations are an inevitably complex matter. This note pays a small tribute to the great contribution made by Anderson (J Wine Econ 15(1):42–70, 2020), with a specific focus on the EU wine sector. This text is far from exhaustive but provides a starting block for a more in-depth analysis into this complex issue. Is wine a niche category within the alcoholic beverages sector? The question is provocative. This may be difficult and complex to answer, but this note provides some "food for thought".
Keywords: E62; I18; P46; Q13; 330; Alcohol; Taxes; Wine policy; Wine regulations